Electrophoretic banding pattern of esterase isozymes in adult brown planthopper Nilaparvata lugens (Stål) (Hom.: Delphacidae) (University Journal of Zoology, Rajshahi University, 2007)
Key words: Esterase; Nilaparvata lugens; isozymes, BPH Univ. j. zool. Rajshahi Univ. Vol.21, 2002. pp. 27-29